Development of E-Booklet Learning Media on Classification of Living Organisms to Improve Scientific Literacy in High School Students - Rahmad; Eka Ariyati; Reni Marlina (Universitas Pendidikan Mandalika, 2026)
This study aims to develop and validate an e-booklet-based learning medium on the classification of living organisms to enhance scientific literacy among high school students. The study employed a Research and Development (R&D) method using a modified Borg and Gall development model consisting of five stages: (1) identifying potentials and problems, (2) data collection, (3) product design, (4) design validation, and (5) design revision. The developed e-booklet was validated by a panel of five experts, including subject matter experts, digital media specialists, and biology practitioners, using a structured Likert-scale instrument. Data were collected through surveys, interviews, and validation questionnaires. The data were analyzed using the Content Validity Ratio (CVR) and Content Validity Index (CVI). The validation results showed that the e-booklet achieved an average CVI value of 1.00, exceeding the critical CVR value of 0.99 from the five validators, indicating strong content validity. The e-booklet integrates various multimedia elements, including relevant texts, images, and videos, to enhance students’ engagement and understanding of biological concepts. The high validity score indicates that the developed e-booklet is feasible for use as a biology learning medium, particularly for teaching the classification of living organisms. These findings demonstrate that the developed digital learning medium is highly feasible and suitable for supporting classroom instruction and independent student learning, aligning with the demands of 21st-century science education.